Surface decoration of bis-aminosilane cross-linked multiwall carbon nanotube ultrafiltration membrane for fast and efficient heavy metal removal - Ravi P. Pandey; Mariam Ouda; P. Abdul Rasheed; Fawzi Banat; Shadi W. Hasan (npj Clean Water, 2022)
Abstract Heavy metals (HMs) are highly toxic water pollutants abundant in industrial wastewater. Herein, a bis[3-(trimethoxysilyl)propyl]amine (BTMSPA) cross-linked multiwalled carbon nanotube (MWCNT) nanomaterial (CQACNT) was synthesized by silanization of MWCNT-OH followed by grafting of positively charged quaternary ammonium groups (glycidyl trimethyl ammonium chloride (GTMAC)) by an epoxide ring-opening reaction. The composite membranes were prepared by the incorporation of CQACNT into the poly(ether sulfone) (PES) polymer matrix. The CQACNT-6 composite membrane exhibited a 3.5-fold increase in pure water permeability (PWP; 312.8 L m−2 h−1 bar−1) as compared to the pristine PES (CQACNT-0) membrane (89.6 L m−2 h−1 bar−1). Moreover, the CQACNT-6 composite membrane showed high HM removal rates (Pb: 89.53%; Ni: 90.42%; Cu: 91.43%; Zn: 91.86%) as compared to the CQACNT-0 membrane (Pb: 39.73%; Ni: 40.32%; Cu: 42.52%; and Zn: 43.91%). After 9 treatment cycles, the CQACNT-6 membrane retained up to 87%, and 94% of its initial PWP and initial Cu2+ rejection, respectively, compared to only 58%, and 54%, respectively for pristine CQACNT-0. The positively charged quaternary ammonium groups enhanced the surface features of PES and MWCNTS, resulting in competitive HM removal rates due to the electrostatic repulsion between the HM and the porous membranes, as well as high PWP.